(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2026)
This study evaluated integrated pest management (IPM) components for controlling four major tea pests (tea mosquito bug, red spider mite, thrips, and looper caterpillar) in Bangladesh through multi-location field and laboratory experiments. The study was conducted at the main farm of Bangladesh Tea Research Institute (BTRI), Srimangal, Moulvibazar, and BTRI Sub Station, Panchagarh, during April 2017 to September 2018. The experiments were set up following a completely randomized design (CRD) in laboratory conditions and a randomized complete block design (RCBD) in field conditions with three replications. Data were collected at 24, 48, and 72 hours after treatment (HAT) at laboratory conditions and 7 days intervals at field conditions following respective methods. The results revealed that under cultural control measures, light pruning (LP) significantly reduced the infestation of pests of tea other than skiff pruning. Seven days of regular plucking rounds reduced the incidence of Helopeltis and other foliar pests of tea. Weeding significantly reduced the infestation of red spider mite in tea. Under mechanical control measures, solar power light traps and yellow sticky traps captured a greater number of thrips, jassids, aphids, moths of the looper caterpillar, and other flying insects in the tea ecosystem. Among the botanical extracts, fresh leaves, succulent stems, and seeds of Bishkatali, Bhat, Burweed, Garlic, Lantana, Mahogani, and Tobacco demonstrated strong insecticidal properties. The host plant resistance trials revealed that clones BT1, BT2, and BT15 were less susceptible to Helopeltis; BT5, BT6, and BT17 showed relatively high resistance to red spider mite, while BT3, BT4, BT8, BT9, BT12, BT13, BT14, BT15, BT18, BT19, and BT20 were less infested by thrips. The bio-control agent, Bracon hebetor, as a larval parasitoid, effectively suppressed looper caterpillar populations. Microbial pesticides Metarhizium anisopliae and Pseudomonas fluorescens significantly reduced red spider mite population, while Bacillus thuringiensis significantly reduced looper caterpillar population. These findings collectively support a robust, eco-friendly IPM framework for sustainable tea cultivation in Bangladesh, reducing pesticide dependency, lowering production costs, and promoting environmental safety. Int. J. Agril. Res. Innov. Tech. 15(2): 1-18, Dec 2025